1988
DOI: 10.1111/j.1399-3054.1988.tb09149.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in coleus in the ability to accumulate abscisic acid in response to water deficit

Abstract: 1988. Genotypic variation in coleus in the ability to accumulate abscisic acid in response to water deficit. -Physiol. Plant. 72: 441-449.Abscisic acid (ABA) concentration and plant and soil water potentials were determined in leaves of three cultivars of Coleus blumei Benth. cvs. Marty, Buckley Supreme and PI3.54190, chosen for their differences in sensitivity to drought, SO, andor chilling stress. Plants were subjected to 'gradual' soil moisture stress (SMS) for 0-6 days, during which time the soil dried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Droughthardy varieties of maize (Larque-Saavedra and Wain 1976) and cotton (Ibragimov et al 1978) produced more ABA when stressed by drought. By contrast, droughtresistant varieties of spring wheat (Quarrie 1981) and coleus (Terry et al 1988) produced less ABA. The present study attempts particularly to explain growth rate differences observed under drought in conifer species.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Droughthardy varieties of maize (Larque-Saavedra and Wain 1976) and cotton (Ibragimov et al 1978) produced more ABA when stressed by drought. By contrast, droughtresistant varieties of spring wheat (Quarrie 1981) and coleus (Terry et al 1988) produced less ABA. The present study attempts particularly to explain growth rate differences observed under drought in conifer species.…”
Section: Discussionmentioning
confidence: 94%
“…Plants vary in their ability to accumulate ABA during water stress (Roberts andDumbroff 1986, Terry et al 1988). Genotypes of pearl millet (Henson et al 1981) and coleus (Terry et al 1988) which accumulated higher amounts of ABA closed their stomata more quickly and fully under water stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that ABA may function as a trigger in cold acclimation: the signal caused by low temperature would result in an increase in endogenous ABA concentration, which in turn would initiate the acclimation process, probably at the level of gene expression [8]. Similar to cold acclimation, drought stress results in increased ABA levels in plant leaves [38] and proteins and mRNAs induced by drought stress are also induced by exogenously added ABA [4,6,33]. It has been suggested that the induction of new proteins by drought is mediated by the increased levels of endogenous ABA [4,6].…”
Section: Introductionmentioning
confidence: 97%
“…Plant material consisted of two cultivars ofColeus found previously to differ in sensitivity to a wide range of stresses, with 'Buckley Supreme' ('BS') being highly sensitive and 'Marty' ('M') being relatively insensitive (Semeniuk and Heggestad, 1981;Semeniuk and Stewart, 1979;Terry et al, 1988). The studies were conducted at Beltsville, MD in a greenhouse equipped with incandescent lights to extend the daylength to 16 h. Maximum daytime photosynthetically active radiation was ca 1,100-1,500 umol-nvV measured at plant canopy height at mid-day.…”
Section: Plant Materials and Cultural Proceduresmentioning
confidence: 99%
“…However, relatively little is known about the adaptability of ornamental species to acid soils high in exchangeable Al (Foy and Wheeler, 1979;Knoblauch, 1981). Previous studies conducted at Beltsville, MD have demonstrated significant cultivar differences in the environmental stress tolerance ofColeus (Abbott et al, 1987;Krizek et al, 1985;Moline and Semeniuk, 1983;Semeniuk and Heggestad, 1981;Semeniuk and Stewart, 1979;Terry et al, 1988). The cultivar 'Buckley Supreme' ('BS') is extremely sensitive to water stress, UV-B radiation, ozone (O 3 ), and sulfur dioxide (SO 2 ), while the cultivar 'Marty' ('M') is tolerant of these stresses.…”
Section: Introductionmentioning
confidence: 97%